2023
DOI: 10.3390/coatings14010015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cyclic Fatigue Resistance of Tia Tornado Blue and Tia Tornado Gold in Curved Canals: In Vitro Study

Ziyad Allahem,
Mohammad Bendahmash,
Reem Almeaither
et al.

Abstract: (1) Background: The aim of this study was to investigate the cyclic fatigue behavior of the newly introduced endodontic instrument systems Tia Tornado Blue and Tia Tornado Gold. (2) Methods: The tested rotary instruments were divided according to their type into four groups as follows: Tia Tornado Blue (TTB), Tia Tornado Gold (TTG), Protaper Gold (PTG), and Vortex Blue (VB). The cyclic fatigue resistance of fifteen instruments of each group, totaling 60, was tested. Each instrument was rotated under continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Tia Tornado Blue (TTB) (Tiadent, Houston, TX, USA) is another novel blue rotary file system made with heat-treated technology. While the manufacturers claim that it has superior torque strength and resistance to cyclic fatigue [17], a previous study showed no improvement in cyclic fatigue resistance in comparison with other blue NiTi files [18]. It is essential to partner mechanical root canal preparation with chemical irrigation to help lubricate files, flush out debris, and most crucially, achieve the disinfection of the root canal system and dissolve pulp tissues without damaging periapical tissues [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tia Tornado Blue (TTB) (Tiadent, Houston, TX, USA) is another novel blue rotary file system made with heat-treated technology. While the manufacturers claim that it has superior torque strength and resistance to cyclic fatigue [17], a previous study showed no improvement in cyclic fatigue resistance in comparison with other blue NiTi files [18]. It is essential to partner mechanical root canal preparation with chemical irrigation to help lubricate files, flush out debris, and most crucially, achieve the disinfection of the root canal system and dissolve pulp tissues without damaging periapical tissues [1].…”
Section: Introductionmentioning
confidence: 99%
“…Limited articles are available on the cyclic fatigue resistance of blue NiTi files [18,27]. However, no studies have examined both cyclic fatigue and torsional resistance of blue NiTi files at body temperature, let alone their performance under conditions simulating clinical situations such as irrigation with NaOCl.…”
Section: Introductionmentioning
confidence: 99%